Defining the concept of reserve in the motor domain: a systematic review - Giustiniani, Andreina; Quartarone, Angelo (Frontiers in Neuroscience, 2024)
A reserve in the motor domain may underlie the capacity exhibited by some patients to maintain motor functionality in the face of a certain level of disease. This form of “motor reserve” (MR) could include cortical, cerebellar, and muscular processes. However, a systematic definition has not been provided yet. Clarifying this concept in healthy individuals and patients would be crucial for implementing prevention strategies and rehabilitation protocols. Due to its wide application in the assessment of motor system functioning, non-invasive brain stimulation (NIBS) may support such definition. Here, studies focusing on reserve in the motor domain and studies using NIBS were revised. Current literature highlights the ability of the motor system to create a reserve and a possible role for NIBS. MR could include several mechanisms occurring in the brain, cerebellum, and muscles, and NIBS may support the understanding of such mechanisms.